2003
DOI: 10.1002/pssb.200301825
|View full text |Cite
|
Sign up to set email alerts
|

The radial breathing mode frequency in double‐walled carbon nanotubes: an analytical approximation

Abstract: We study the breathing-like phonon modes of double-walled carbon nanotubes in a simple analytical model by considering the tube walls as coupled oscillators. The force constant of the oscillator coupling is found to be proportional to the inner tube diameter. Thus, only for small-diameter tubes, the shift of the breathing-like phonon mode frequencies (relative to the radial breathing modes of the isolated layers) scales with the tube diameter D. For tubes with larger diameter the in-phase breathing-like phonon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 13 publications
3
38
0
Order By: Relevance
“…The collective RBM oscillations of a unit-length DWNT can be modelled by a coupled mechanical oscillator with five parameters: m i , k i , m o , k o and k c (Fig. 3a) 25 . The unit-length mass of the inner-and outerwalls (m i and m o ) can be obtained directly from the tube chiral indices, and the unit-length intrinsic force constant of the two walls (k i and k o ) can be obtained from RBM frequencies of isolated SWNTs (Supplementary Note S1).…”
Section: Resultsmentioning
confidence: 99%
“…The collective RBM oscillations of a unit-length DWNT can be modelled by a coupled mechanical oscillator with five parameters: m i , k i , m o , k o and k c (Fig. 3a) 25 . The unit-length mass of the inner-and outerwalls (m i and m o ) can be obtained directly from the tube chiral indices, and the unit-length intrinsic force constant of the two walls (k i and k o ) can be obtained from RBM frequencies of isolated SWNTs (Supplementary Note S1).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that continuum approach works remarkably well even for nanometer thick semiconductor structures and single wall carbon nanotubes. [16][17] Due to the fact that the length of the viruses is much larger than their diameter, we model TMV and M13 as infinite cylinders (see Fig. 1).…”
Section: Analytical Approachmentioning
confidence: 99%
“…Accordingly, the elements of submatrices D αβ are much less than those of D αβ (unless α = β), and may be considered as a perturbation to the dynamical matrix of the noninteracting walls. This invokes fruitful interpretation of CDWNT modes in terms of the modes of the isolated layers [54,65]. …”
Section: Perturbative Interpretationmentioning
confidence: 99%
“…2.19), being mutually well separated by frequency. The frequencies of the resulting [65] in-phase and out-ofphase breathing-like (BL) modes are found by substituting frequencies (2.37) in (2.42). The numerical results [66], well fitted by κ BL = −246404 + 38799D, are in accordance with earlier predictions [54] and match the experimen- tal results [69][70][71].…”
Section: Breathing-like and High-energy Modesmentioning
confidence: 99%